District Census Handbook, Mandya, Part XIII-A & B, Series-9 - Das, B.K. (Karnataka, 1981)
Village Directory, Town Directory, Status and Growth History, Physical Aspects and Location of Towns 1979, Municipal Finance 1978-79, Civic and Other amenities in ntified slume medical Educational Recreational and cultural Facilities 1979.
Keywords: Village and town Directory; Village and townwise Primary Census Abstract